The water footprint of English beef and lamb production - Chatterton, Julia C.; Hess, Tim M.; Williams, Adrian G. (Cranfield University, 2011)
Recent reports highlighting large quantities of water required to produce a kilo of meat have attracted media attention, leading to debates over the role of meat in a sustainable diet. Such reports frequently quote figures based on global averages and therefore conceal significant regional variation, ignoring the source of the water required and local climatic conditions. This report attempts to quantify the water footprint of English beef and lamb production, combining the water simulation model Wasim and the Cranfield Life Cycle Assessment model to calculate the water required to produce a tonne of beef and lamb meat. This method accounts for all water required by grass and crops in addition to drinking water and other requirements. Water use is considered in three categories; green, blue and grey water. Results show that beef has a water footprint of 17,700 m3/t carcase weight and lamb 57,800 m3/t. Of these, 84% and 97% respectively is green water use, i.e. evapotranspiration of rainfall on crop and grassland. Without this breakdown there is no distinction between rainfall and irrigation supply (blue water), which means that UK beef production may appear similar in impact to countries where irrigation of feed crops is dominant. This report highlights the importance of considering water use in context; in this case, for a temperate, wet climate such as England where crop and grassland water requirements are adequately met by green water from rainfall. Upland and hill production systems have higher water footprints, mostly because grass yield is lower. However, it is shown that rainfall surplus per tonne grass production is still highest in these regions, so that export of water for other human purposes is possible from these regions.
Keywords: Water footprint; Beef; Lamb; meat